'SEMINAR ON ISLAMIC HEALING 2017 - SANTAU' WILL NOT BE HELD AT USM - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
Universiti Sains Malaysia (USM) will not be hosting the 'Seminar on Islamic Healing 2017 Santau' at the USM Main Campus in Penang as reported earlier.